نموذج التنمية الوطنية المستقلة المعتمدة على الذات " النموذج البديل للاقتصاد السوري " (Latakia University Journal - Economic and Legal Sciences Series, 2013)
تعاني الدول النامية (ومنها سورية) تخلفاً نتيجة السياسات الاقتصادية المعتمدة، وتزايد التبعية للقوى المالية والاقتصادية الدولية، فضلاً عن ازدياد الأهمية للاقتصاد الريعي والمضاربات المالية، مقابل تراجع طردي في أهمية القطاعات الإنتاجية الزراعية والصناعية، ما أسفر عن تزايد الانكشاف على الخارج. مما يجعل التنمية الوطنية المستقلة المعتمدة على الذات ضرورة تاريخية لتصحيح المسار التنموي بإعادتها الاعتبار إلى مفهوم الدولة التنموية، التي غابت عن الدول النامية، وغاب معها دورها في الريادة والتوجيه للخروج من التخلف والتبعية. ومن هذا المنطلق ركزت الخطة الخمسية العاشرة على ضرورة الإصلاح الاقتصادي بهدف تحقيق التنمية الاقتصادية والاجتماعية، ومن هنا كان السؤال الأول المطروح في بحثنا يدور هل حققت الخطة التنموية القائمة على السياسات الليبرالية الجديدة أهدافها خلال الفترة 2006-2010، وللإجابة على هذا السؤال قمنا بتحليل المؤشرات الاقتصادية والاجتماعية المحققة ومقارنتها مع ما هو مخطط، ومن خلال الدراسة توصل الباحث إلى أن الخطة الخمسية العاشرة لم تحقق الأهداف المنشودة، مما فرض ضرورة البحث عن نموذج بديل للاقتصاد السوري يحقق التنمية الاقتصادية والاجتماعية، ومن هنا كان السؤال الثاني هل يمكن تحقيق التنمية الوطنية المستقلة، وللإجابة على هذا السؤال قمنا بتحليل أبرز نقاط القوة الاقتصاد السوري (تنوع القطاعات الاقتصادية، وانخفاض الدين، واحتياطيات دولية كبيرة..) والتي تعد من أهم المقومات التي تدعم التنمية الوطنية المستقلة، التي تمكننا في حال استثمارها بالشكل الأمثل من الاعتماد عليها في معالجة نقاط الضعف في الاقتصاد السوري.Developing countries (including Syria) suffer backward as a result of economic policies adopted, and the growing dependency of the international financial and economic forces , as well as the increasing importance of the income economy and financial speculation, against a progressive decline in the importance of productive agricultural and industrial sectors , which resulted in increased exposure to the outside. making self-reliant independent national development a historical necessity to correct development path and return it into consideration to the concept of the developmental state, which were absent from the developing countries, and missed her role in the leadership and direction to get out of underdevelopment and dependency. In this sense the tenth five-year plan focused on the need for economic reform in order to achieve economic and social development, and here was the first question posed in our study whether a development plan based on the neo-liberal policies objectives during the period 2006-2010, achieved its targets. To answer this question, we analyzed the economic and social indicators achieved and compare it with what is planned, and through the study, the researcher concluded that Tenth Five Year Plan did not achieve the desired objectives, forcing the need to search for an alternative model of the Syrian economy to achieve economic and social development, hence the second question can we achieve national development independence, and to answer to this question, we analyzed the most prominent strengths Syrian economy (diversity of economic sectors, low debt, and large international reserves ..) which is one of the most important ingredients that supports national development Independent, which enables us if invested optimally from reliable in addressing weaknesses in Syrian economy.